1993
DOI: 10.1002/art.1780360814
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoproliferation in primary sjögren's syndrome. evidence of selective expansion of a b cell subset characterized by the expression of cross‐reactive idiotypes

Abstract: Objective. To evaluate the possibility that lymphoproliferation in primary Sjogren's syndrome (SS) arises within a subset of B cells.Methods. A panel of monoclonal antibodies (MAb) specific for rheumatoid factor (RF)-associated cross-reactive idiotypes (CRI) and anti-V, and anti-V, subgroup antibodies were used to define the clonality of B lymphocytes undergoing neoplastic transformation in 5 patients with primary SS. Anti-CRI antibodies were also used to study longitudinal variations in serum paraprotein leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

1994
1994
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 36 publications
1
13
0
4
Order By: Relevance
“…Previous studies of IgM RF L chains in RA, HID and MC RF revealed a bias towards (80-93%) rather than L chains [8,14]. Similarly, RFs in SS peripheral blood as well as the B cells infiltrating the salivary glands of SS were shown previously to be biased towards L chains [25][26][27]. The predominant usage of L chains in these RFs is also associated with a restricted utilization of V 3 family genes.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies of IgM RF L chains in RA, HID and MC RF revealed a bias towards (80-93%) rather than L chains [8,14]. Similarly, RFs in SS peripheral blood as well as the B cells infiltrating the salivary glands of SS were shown previously to be biased towards L chains [25][26][27]. The predominant usage of L chains in these RFs is also associated with a restricted utilization of V 3 family genes.…”
Section: Discussionmentioning
confidence: 87%
“…[31] to be recognized by G6, an mAb which defines an overlapping but distinct CRI to G8 frequently present on RF paraprotein [23]. As shown in Table 1 16 mutations (1 mutation/779 bp) have been observed.…”
Section: Anti-cd40 + Il-4-driven Clonal Expansion Of Naive Human B Cementioning
confidence: 99%
“…In general, however, this 1977 report continues to be applicable today with more recent reports detailing presentations of monoarticular and pauciarticular arthritis [7][8][9][10][11][12]. A different line of clinical research has addressed the relationship of both classical rheumatoid arthritis and Sjogren's syndrome with lymphoma [13,14]. Fortin [15] has suggested that this increasingly fruitful area of research may link basic mechanisms of immune surveillance with more current concepts of programmed cell death (apoptosis) and speculated that unifying mechanisms of pathogenesis may be elucidated in the near future.…”
Section: Articular Syndromesmentioning
confidence: 84%